Gamma irradiated starch based hydrogel impregnated with silver nanoparticle - Esalami, Fayezeh; Ahmad, Zuraida; Abdul Razak, Nur Humairah (Trans Tech Publications, Switzerland, 2015)
Hydrogel based on petroleum polymer are expensive, non-biodegradable and nondecompose which lead them to heavy waste in environment. In this paper, biopolymer is used to overcome this problem and promote environmental friendliness and biocompatible to the human skin and impregnation of silver nano-particle (SNP) acts as anti-bacterial which needed for this application. The hydrogel is prepared by mixing the solution of sago starch with polyvinyl alcohol solution for polymeric grafting before impregnated with the SNP and finally this solution is subjected to the gamma irradiation. The irradiated starch based hydrogels is evaluated for its swelling properties, chemical functionalities and phase analysis. The hydrogels produced from this method is observed high in transparency and swelling behaviour as well as high water absorbency.